Questions of English : Your Questions about the English Language answered by the Oxford Dictionaries team - Marshall, Jeremy; McDonald, Fred (Oxford University Press, 1994)
The Oxford Word and Language Service (OWLS for short) was launched by the Oxford University Press on the Ides of March, 1983. The first enquiries began to arrive almost before the ink was dry on the press release, and since then the lexicographers have answered a truly enormous number of queries about the origin, meaning, and use of English words.